The Opposition Bourgeoisie Ideology in Titanic Movie - Waode Nurhandi; Nur Israfyan Sofian (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2024)
This study aims to analyze the opposition as reflected in the Titanic movie. The research used the descriptive qualitative method. The source of data in this research was taken from Titanic movie by James Cameron as data as primary data and a journal, literature, books, and some articles as secondary data. This research uses the theory of Marxism from Karl Marx which is used as a tool to analyze the finding and the opposition against bourgeoisie ideology in Titanic movie. The result of the research shows that there are two types of social class in the Titanic movies. Based on the findings and discussion, the research found 14 data on the relations between the bourgeoisie and the proletariat, 9 data on the class consciousness, 10 data on the opposition, and 8 data on The Paradox of Jack and Rose. The researcher concluded based on the result of the research that has been done and found 41 data that included the opposition against bourgeoisie ideology in Titanic movie.